On the salinity structure in the South Adriatic as derived from float and glider observations in 2013–2016. (January 2020) - Kokkini, Z.; Mauri, E.; Gerin, R.; Poulain, P.M.; Simoncelli, S.; Notarstefano, G.
Abstract: Between 2013 and 2016 a drastic change in the vertical salinity structure in the South Adriatic Pit was recorded by Argo floats and ocean gliders. The analysis revealed that high salinity waters characterised 2013 at the surface and intermediate layers, creating the conditions for dense water formation. The year 2014 was instead marked by less saline water, dominant in the first 100 m, that spread in the entire Pit. Heat gain, negative E-P anomalies and abundant river runoff, during that period, maintained this saline stratification for more than a year. This water mass contributed to the dilution of the underlying layer, during the convection event of 2015. The spring transition period, later in 2015, as defined by new saline water placed over the winter formatted water mass and the unperturbed part of the existent salinity profile, in the deeper layers, resulted in a particular vertical structure, characterised by a double salinity maximum. High salinity waters continued to be present at the surface and intermediate layers until the end of 2016, when the strong convection led to a deep mixing, eliminating that structure. The analysis of the available datasets in the South Adriatic Pit, since 1984, linked the presence of these high salinity waters, with the cyclonic phase of the North Ionian Gyre, additionally revealing, also, years of a decreasing trend, during the anticyclonic mode of the Gyre.